Multivariate analysis of Per capita availability of nutrients in 44 countries - Curi, Paulo Roberto; Terada, Lucia; Beckers, Patrick Johannes; Alves, Alexandre (Pesquisa Agropecuaria Brasileira, 1992)
The situation of the countries is studied based on the availability of the animal and vegetal nutrients (data published by FAO in 1988). Two multivariated statistical methods were used: Principal Components Analysis and Cluster Analysis. The study was applied to countries of all the continents, with 44 countries of the most different degrees of development. The first principal component was interpreted as a measure of the available animal nutrients, and the second principal component as a vegetal nutrient, wich made it possible the ordering of the countries. The most discriminating variables were the protein, calorie, riboflavin, fat and calcium of animal origin and the less ones were niacin, beta carotene, equivalent retinol and calorie of vegetal origin.